2015
DOI: 10.1515/pomr-2015-0026
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Accuracy of SRTM Dem and Aster Gdem Datasets for the Coastal Zone of Shandong Province, Eastern China

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…This was also identified by Sharma et al (2014) who reported that ASTER DEM tends to smooth the altitudes in flat areas. Similar results were found by Luana et al (2015) when comparing ASTER DEM, SRTM 30 DEM and elevation points at 1:50,000 scale in a watershed located in Shandong Province, China. The RMSE values obtained for the SRTM DEMs (Figure 2) are in agreement with those found in literature.…”
Section: Relief Characterization and Performance Of The Different Relief Sources Based On Statistical Measuressupporting
confidence: 83%
“…This was also identified by Sharma et al (2014) who reported that ASTER DEM tends to smooth the altitudes in flat areas. Similar results were found by Luana et al (2015) when comparing ASTER DEM, SRTM 30 DEM and elevation points at 1:50,000 scale in a watershed located in Shandong Province, China. The RMSE values obtained for the SRTM DEMs (Figure 2) are in agreement with those found in literature.…”
Section: Relief Characterization and Performance Of The Different Relief Sources Based On Statistical Measuressupporting
confidence: 83%
“…These AEZs are locally referred to as Weyna Dega (subtropical) (1500-2300 m.a.s.l), Dega (temperate) (2300-3200 m.a.s.l) and High Dega (Alpine) (3200-3700 m.a.s.l) [76]. Because of its good vertical and horizontal precision, this classification was performed using a 30 m SRTM DEM spatial resolution [78]. To improve agricultural development planning, agronomic zoning is generally significant, as agronomic regions are heavily dependent on climatic parameters such as rainfall quantity and variability, temperature, and vegetation characteristics [76].…”
Section: Belg and Kiremit Season Yearly Variation Of Vegetation Condimentioning
confidence: 99%
“…Noise errors (local variability) are also a characteristic of both DEMs, while the ASTER GDEM V2 exhibits more high frequency noise than V1 overall and as the (although limited) SRTM-1 DEM examples [53]. While vegetation and tree canopy are present in both DEMs [68,69], it is stated that GDEM2 has higher elevations than SRTM in many forested areas [53,69] and that higher slopes and elevation are correlated with errors in SRTM DEMs [70,71] and ASTER GDEM V2, but less strong [14] or not apparent in the case of elevation [53]. Further, SRTM DEMs tend to overestimate valley-floor elevation and underestimate ridge elevation [62,72].…”
Section: Demsmentioning
confidence: 99%